Bismuth-Mediated Arylation of Weak Nucleophiles - Ruffell, Katie (2023)
Building upon recent advances in bismuth-mediated arylations which have seen the development of mild transmetallation procedures and utilisation of bismacycle scaffolds, several methodologies for the bismuth-mediated arylation of weak nucleophiles have been established.